THE INFLUENCE OF THE NET PROFIT OVER THE INVESTMENT DECISION MAKING - Mihaela GADOIU; Mariana BANUTA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2017)
This article aims at analysing how the investment decision is influenced by the final result of the activity of an entity after paying the profit tax. Starting from the need to make investments in order to ensure the economic efficiency and subsequently the economic growth, we sought to capture both the advantages and the disadvantages of the various versions that must be considered for the selection of the investment project. From the perspective of the presentation of this topic, we have analysed, in addition to the aspects related to the notion of investment, the investment typology, the decision to invest in a certain environment, and a number of economic and financial indicators used in order to make an investment decision.